MINDFULNESS BASED STRESS REDUCTION (MBSR) TERHADAP PENURUNAN BURNOUT PADA PERAWAT - Sarah Fatimah Azzahra; Evany Victoriana; Maria Yuni Megarini (JIP (Jurnal Intervensi Psikologi), 2023)
ABSTRACT: Nurse is one of the professions engaged in the health sector and has a high intensity to deal directly with patients. The many responsibilities, the high complexity of the work and the demands that must be carried out by nurses make the nursing profession vulnerable to stress and burnout at work. This study aims to determine the effect of mindfulness-based interventions on reducing burnout in nurses at "X" Hospital, Bandung City. This study used the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) and the Five Facet Mindfulness Questionnaire (FFMQ) as a manipulation check. This study uses an experimental method to look for the effect of intervention mindfulness-based stress reduction (MBSR) as the independent variable to reduced burnout as the dependent variable. The results showed that there was a significant effect of mindfulness-based interventions through the mindfulness-based stress reduction (MBSR) method on reducing burnout in burnout nurses at "X" Hospital, Bandung City.